Do organizational conditions influence teacher implementation of effective classroom management practices: Findings from a randomized trial. (February 2019) - Sebastian, James; Herman, Keith C.; Reinke, Wendy M.
Abstract: Although there is a growing evidence base about effective classroom management practices, teacher implementation of these practices varies due to a number of factors. A school's organizational health is one aspect of the broader social environment that has been hypothesized to influence implementation of interventions. Yet, empirical evidence is limited on whether organizational contexts can influence teacher implementation of effective interventions and subsequently, classroom environments and student outcomes. In the present study, teachers in an urban school district were randomly assigned to receive training in the Incredible Years Teacher Classroom Management program (IY TCM), a classroom management intervention. We examined how teacher perceptions of their school environment moderated intervention effects for previously established treatment outcomes – implementation of effective classroom methods, students' social behaviors, emotional regulation, and social competence. Results showed that treatment effects on teacher implementation and student outcomes were moderated by teachers' sense of affiliation to their school. Specifically, main effects on implementation of effective classroom management strategies were only observed among teachers whose perceptions of initial teacher affiliation was low or average; whereas main effects on student outcomes were only found for teachers with initial high levels of affiliation.